2017
DOI: 10.5296/ber.v7i1.10936
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Information Communication Technology on Stock Market Capitalization: A Panel Data Analysis

Abstract: The level of investment in information communication technologies (ICT) that may affect Business and Economic Research ISSN 2162-4860 2017 http://ber.macrothink.org 262 stock market capitalization varies substantially across countries. Using data on 81 countries from 1998 to 2014, we use a country-fixed effects model to estimate the relationship between ICTs and stock market capitalization. Our empirical model is built on the premise that (1) increased deployment of ICT allows financial market participants to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 17 publications
0
2
0
1
Order By: Relevance
“…In this study, we focus on the bilateral interplay between ICT indicators and stock market development considering the gap in the empirical literature. In the related empirical literature, Lee et al (2017), Afshan et al (2020), Igwilo and Sibindi (2022), and Suragan and Durmuşkaya (2022) uncovered a positive effect of various ICT indicators on stock market development. Furthermore, Pradhan (2014) revealed a bidirectional causal relationship between ICT and stock market development.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we focus on the bilateral interplay between ICT indicators and stock market development considering the gap in the empirical literature. In the related empirical literature, Lee et al (2017), Afshan et al (2020), Igwilo and Sibindi (2022), and Suragan and Durmuşkaya (2022) uncovered a positive effect of various ICT indicators on stock market development. Furthermore, Pradhan (2014) revealed a bidirectional causal relationship between ICT and stock market development.…”
Section: Literature Reviewmentioning
confidence: 99%
“…On the other hand, Okwu (2015) investigated the effect of ICT on Nigeria and South Africa over the 1995-2014 period through regression and found that ICT indicators had an insignificant impact on stock market capitalization, but mobile telephone subscriptions had a positive impact on value of traded shares and number of personal computers had a positive effect on stock market liquidity. Lee et al (2017) examined the relationship between ICT indicators and stock market development in 81 countries over the period 1998-2014 through regression and found that ICT development is positively associated with stock market capitalization. On the other hand, Lee et al (2019) examined the relationship between ICT and stock market efficiency in 71 countries between 2002 to 2014 through regression and revealed that stock markets in countries with high ICT diffusion are efficient while stock markets in countries with low or medium ICT diffusion are not all efficient.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The study concludes that ICT penetration is helpful both in the stock market traded and consumer market, which does not affect the face value of stakeholders in both dimensions. Lee, Alford, Cresson, and Gardner (2017) used the panel analysis of 81 countries to evaluate the dynamic linkages between ICTs penetration and stock market capitalization during a period of 1998–2014. The results show that ICTs helpful to improve stock trading and reduced asymmetric information, while it reduces the inherent risks associated with the uncertainty in financial markets that further improve economic fundamentals across countries.…”
Section: Introductionmentioning
confidence: 99%
“…Economists point in addition to the role of geography and technology. They highlight the advantages of a network of information and communications links for completing a high volume of financial transactions and thereby reaping economies of scale (Lee, Alford, Cresson, & Gardner, ). They single out geography as a factor influencing access to that network (Eichengreen, Lafargette, & Mehl, ).…”
Section: Introductionmentioning
confidence: 99%